Uncertain new technologies – economics of ground effect vehicle operator - Hilmola, Olli-Pekka; Heljanko, Ekku (Business: Theory and Practice, 2025)
New technologies and vehicle types have become available for transportation and logistics in the recent decade. One of the such is Ground Effect Vehicle (GEV), which in new reinvented form is using electric propulsion, new lighter materials and could be without onboard pilots. These could be used in coastal and archipelago types of areas, where distances are relatively short. In this research is introduced economic and business case evaluation of GEV in the context of Canary Islands. Aim is to build understanding from financial success of GEV. Simulation model incorporates number of uncertainties, like usage life-cycle of fleet, fleet investment cost, interest rates, lower cargo volume development in the early years and possibility for passenger transports. Analysis shows that success depends quite much on cargo pricing, and the interest of customers to pay premiums from faster delivery. Being operator of GEV offers possibility for profitability, but if most of uncertainties take place, then investments might increase too much and result on significant losses. Research provides added value on discipline development and better alternative on spreadsheet and cost focused models.